Industrial math program gets nod from expert panel - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Safriza, Baharuddin; Mohamad Najib, Mohammad Nor; Noor Azhar, Abd. Rasid; Nurul Nadia, Abd Razak (Penerbit UMP, 2009)
JAN 20-22 KUALA LUMPUR: An expert panel workshop with senior academics and industry mathematicians was again held at the Concorde Inn, Sepang, chaired by Deputy Vice-Chancellor(Academic & Internationalization), Professor Dr. Sabarudin Mohd.